Phylogeography Study of the Siberian Apricot (Prunus sibirica L.) in Northern China Assessed by Chloroplast Microsatellite and DNA Makers - Zhe Wang (Frontiers in Plant Science, 2017)
There is evidence that a band of dry climate separated plants in East Asia into distinct northern and southern groups. However, few studies have focused on the arid belt in this region, especially with regard to plants. We analyzed genetic variation in 22 populations of Siberian apricot (Prunus sibirica L.), a temperate deciduous species distributed in this arid belt, using two chloroplast DNA (cpDNA) sequences, seven chloroplast microsatellite loci (cpSSRs), and 31 nuclear microsatellite loci (nSSRs), to study its phylogeography. Chloroplast data showed the complete fixation of two different genetic groups: the eastern and western groups. Genetic differentiation between the two groups was significant (FST = 0.90925, p < 0.01). This pronounced phylogeographic break was also indicated by nSSR data, but there were disparities regarding individual populations. An asymmetric gene flow via pollen and seeds likely resulted in discordance between the present-day geography of nuclear and chloroplast lineages. There was a distinct boundary between the two large groups, which were fixed for two of the most ancestral chlorotypes. Two populations with the highest chloroplast genetic diversity were located in the Yanshan Mountains and Jinzhou, considered to be the glacial refugia. The split of chloroplasts between the eastern and western groups was estimated to have occurred ~0.1795 Ma, whereas nuclear divergence occurred approximately 13,260 years ago. Linear regression analysis showed that climatic factors (annual precipitation and annual mean temperature) had a significant correlation with mean ancestry value (P < 0.05) indicated that they were potential factors for the formation of the two groups. In addition, this boundary was a contact zone between two groups from different refugia.